Case Report: Idiopathic Sclerosing Orbital Inflammation. Issue 4 (April 2021) - Bachman Groth, Jane A.; Harris, Gerald J.
Abstract : SIGNIFICANCE: Idiopathic sclerosing orbital inflammation (ISOI) is characterized by insidious, chronic, progressive inflammation and fibrosis that damage ocular structures and produce a mass effect. This case highlights the challenges in diagnosis and management of ISOI, as well as the associated ocular morbidities, including potential vision loss. PURPOSE: The purpose of this study was to provide education regarding a rare condition that exhibits variable presentation and has an unpredictable success rate with regard to treatment paradigm. Improved therapeutic options are promising. Ultimately, early detection and management are key and may allow for better visual outcome. CASE REPORT: A 46-year-old woman presented with complaints of chronic right-sided facial headaches and eye pain and gradual right globe prominence over the previous 6 months. Worsening vision and decreased right peripheral visual field were also noted. Upon examination, an afferent pupillary defect and florid disc edema were evident. Imaging studies revealed an orbital and extraorbital infiltrative mass involving the right orbital apex, inferior orbital fissure, pterygopalatine fossa, and cavernous sinus. Right anterior orbitotomy with biopsy revealed fragments of fibroconnective and adipose tissue with sclerosis and chronic focal inflammation, consistent with ISOI. Treatment included intravenous methylprednisone, followed by oral prednisone, beginning at 60 mg/d with a slow taper thereafter. Signs and symptoms improved dramatically and eventually resolved. Vision significantly improved, and the afferent pupillary defect resolved. The patient remained asymptomatic at 3-month follow-up. CONCLUSIONS: Idiopathic sclerosing orbital inflammation is difficult to diagnose and manage. No large studies exist because of the rare nature of the disease. Slowly progressive, nonspecific signs and symptoms may delay recognition and treatment. Orbital imaging and histopathologic analysis are critical for definitive diagnosis. Conventional treatment with corticosteroids is not uniformly successful, but newer combined therapy options can improve outcomes. Early identification and treatment are key to management and ultimate preservation of function and vision.